Feedback and Direction Sources Influence Navigation Decision Making on Experienced Routes - Li, Yu; Li, Weijia; Yang, Yingying; Wang, Qi (Frontiers in Psychology, 2019)
When navigating in a new environment, it is typical for people to resort to external guidance such as GPS, or people. However, in the real world, even though navigators have learned the route, they may still prefer to travel with external guidance. We explored how the availability of feedback and the source of external guidance affect navigation decision-making on experienced routes in the presence of external guidance. In three experiments, participants navigated a simulated route three times and then verbally confirmed that they had learned it. They then travelled the same route again, accompanied with no, correct, or incorrect direction guidance, which latter two were provided by a GPS (Exp.1), a stranger (Exp.2), or a friend (Exp.3). Half of the participants received immediate feedback on their navigation decisions, while the other half without feedback did not know if they had selected the correct directions. Generally, without feedback, participants relied on external guidance, regardless of the direction sources. Results also showed that participants trusted the GPS the most, but performed best with their friends as a direction source. With feedback, participants did not show differences in performance between the correct and incorrect guidance conditions, indicating that feedback plays a critical role in evaluating the reliability of external guidance. Our findings suggest that incorrect guidance without any feedback might disturb navigation decision-making, which was further moderated by the perceived credibility of direction sources. We discuss these results within the context of navigation decision-making theory and consider implications for wayfinding behaviors as a social activity.